2021
DOI: 10.1093/cdn/nzab008
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic α-Tocopherol Modulate the Neuroinflammatory Response in the Spinal Cord of Adult Ttpa-null Mice

Abstract: Background Vitamin E (α-tocopherol, α-T) deficiency causes neurological pathologies. α-T supplementation improves outcomes, but the relative bioactivities of dietary natural and synthetic α-T in neural tissues are unknown. Objective To assess the effects of dietary α-T source and dose on oxidative stress and myelination in adult Ttpa−/− mice cerebellum and spinal cord. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We chose to focus on the brain and heart for our analyses, as an abundance of research supports vitamin E’s antioxidant role in these tissues [ 3 , 31 , 35 , 38 ]. The correlation between cardiovascular disease/immune systems and αT has been examined in epidemiological, animal, and human studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We chose to focus on the brain and heart for our analyses, as an abundance of research supports vitamin E’s antioxidant role in these tissues [ 3 , 31 , 35 , 38 ]. The correlation between cardiovascular disease/immune systems and αT has been examined in epidemiological, animal, and human studies [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, genotype groups were fed a VED diet, and study results showed that Ttpa +/+ mice maintained some αT in tissues and serum over this time period [ 33 , 35 ]. In Ttpa −/− mice, serum and some peripheral tissues, such as liver and adipose tissue, were not completely devoid of vitamin E whereas in other tissues vitamin E was depleted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations